What predicts U.S. recessions? - Weiling Liu; Emanuel Moench (Federal Reserve Bank of New York, 2014)
We reassess the predictability of U.S. recessions at horizons from three months to two years ahead for a large number of previously proposed leading-indicator variables. We employ an efficient probit estimator for partially missing data and assess relative model performance based on the receiver operating characteristic (ROC) curve. While the Treasury term spread has the highest predictive power at horizons four to six quarters ahead, adding lagged observations of the term spread significantly improves the predictability of recessions at shorter horizons. Moreover, balances in broker-dealer margin accounts significantly improve the precision of recession predictions, especially at horizons further out than one year.
Keywords: C52; C53; E32; E37; 330; recession predictability; ROC; term spread; leading indicators; efficient probit estimator